DEPRESSION IN FAMILY MEMBERS OF ALCOHOL DEPENDENCE PATIENTS: AN OBSERVATIONAL STUDY - MAHAJAN, PIYUSH; DAHUJA, MALVIKA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of the study was to find out prevalence and severity of depression in family members of alcohol-dependence patients. Methods: This was a cross-sectional, observational study in which 50 family members of patients with alcohol dependence according to mental and behavioral disorders diagnostic criterion for research (ICD-10 DCR) included on the basis of a predefined inclusion and exclusion criteria. The severity of alcohol dependence was assessed by Alcohol Use Disorders Identification Test-C (AUDIT-C) score. The incidence of depression and its severity in family members was assessed by Hamilton Rating Scale for Depression (HAM-D) score. The correlation of AUDIT-C score in alcohol-dependent patients and HAM-D score in family members was done by using Pearson coefficient correlation statistical purposes p<0.05 was considered as statistically significant. Results: Out of the 50 patients with alcohol dependence, 48 (96.00%) were males and 2 (4%) were females. The mean age of the patients was found to be 41.12±11.02. The mean duration of alcoholism was 8.16±5.39 years. 19 (38%) patients had AUDIT-C score of 8 whereas AUDIT-C score of 10 and 12 was found in 16 (32%) and 15 (30%) patients each. The most commonly affected relative was spouse (40%), followed by mother (26%), brother (20%), and father (14%). Majority of the family members (82%) had mild depression (score between 8 and 13). Nine (18%) patients did not have any depression. Moderate, severe, or very severe depression was not seen in any family member. There was a significant positive correlation between AUDIT-C score in alcohol-dependent patients and HAM-D score in family members (R score=0.6333 and p<0.005). Conclusion: There is a significant psychological impact, particularly depression, of alcohol dependence on family members. Severity of hazardous drinking correlated positively with the incidence of depression in family members.